Re-Examination of Verb-Predicated Sentence Structure: A Household Syntax Perspective - Roni, Roni (Proceeding of International Joint Conference on UNESA, 2025)
Sentence, as a system, consists of several parts in the form of words that are interrelated with each other to form a unity, thereby creating a sentence system. However, there is no clear concept determining a sentence formulation as a system. This research aims to formulate the system formula in verb-predicated sentences with the analogy of the household system. This descriptive qualitative research discusses the theory of formulation. The result is the concept of a sentence system formula. From the results of the theoretical study and discussion, it can be explained that in verb-predicated sentences, the system formula can be analogous to a household consisting of a mother, biological children, and adopted children. These three parts form a single unit that constitutes a family system. The mother is a part of the household that controls both biological and adopted children. In the sentence, the predicate acts as the mother, while the subject and object are analogous to biological children, and adverbs and complements are analogous to adopted children. The predicate controls the existence of the subject and object because the predicate creates both. The decisive syntactic role of the subject and object is the predicate. The predicate does not make adverbs and complements, but their existence is parallel to the subject and object. Adverbs and complements bind themselves to the predicate through the syntactic roles they carry. Syntactic functions can be positioned as subject and object, while adverbs and complements are not syntactic functions, but both are parallel to syntactic functions.